Liver transplantation from 73-year-old cadaveric donor - M. N. Kornilov; M. G. Minina; I. A. Miloserdov; D. N. Kruglov; R. S. Chaikin; A. G. Malakhov; S. I. Zubenko; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2017)
Orthotopic liver transplantation is the only way to cure chronic liver failure and certain liver tumors. Deceased donor organs are the prevailing source in most transplantation centers. However, there is an organ shortage because of the increasing number of patients in need of transplantation. Using expanded criteria deceased donors is a routine way to overcome organ shortage. The majority of transplantation centers take older donors depending on the local rules. Successful liver transplantation from 73-year-old deceased donor. Recipient suffered from liver neuroendocrine tumor without signs of extrahepatic spread. Liver function is adequate during 90-day follow-up. Liver transplantation from older deceased donors has good outcome according to world experience. Careful donor-recipient selection is the key to success. The first positive trial in our center enlightens the way for further practice.